Effect of an vitamin D deficiency on depressive symptoms in child and adolescent psychiatric patients – a randomized controlled trial: study protocol - Föcker, Manuel; Antel, Jochen; Grasemann, Corinna; Führer, Dagmar; Timmesfeld, Nina; Öztürk, Dana; Peters, Triinu; Hinney, Anke; Hebebrand, Johannes; Libuda, Lars (BMC Psychiatry)

Do Android Taint Analysis Tools Keep their Promises? - Pauck, Felix; Bodden, Eric; Wehrheim, Heike (arXiv:1804.02903)
In recent years, researchers have developed a number of tools to conduct taint analysis of Android applications. While all the respective papers aim at providing a thorough empirical evaluation, comparability is hindered by varying or unclear evaluation targets. Sometimes, the apps used for evaluation are not precisely described. In other cases, authors use an established benchmark but cover it only partially. In yet other cases, the evaluations differ in terms of the data leaks searched for, or lack a ground truth to compare against. All those limitations make it impossible to truly compare the tools based on those published evaluations. We thus present ReproDroid, a framework allowing the accurate comparison of Android taint analysis tools. ReproDroid supports researchers in inferring the ground truth for data leaks in apps, in automatically applying tools to benchmarks, and in evaluating the obtained results. We use ReproDroid to comparatively evaluate on equal grounds the six prominent taint analysis tools Amandroid, DIALDroid, DidFail, DroidSafe, FlowDroid and IccTA. The results are largely positive although four tools violate some promises concerning features and accuracy. Finally, we contribute to the area of unbiased benchmarking with a new and improved version of the open test suite DroidBench.

Pattern based development of digital platforms - Drewel, Marvin; Gausemeier, Jürgen; Koldewey, Christian; Özcan, Leon (Proceedings of the 2018 ISPIM Connects)

Business Model Portfolio Planning for Smart Services - Koldewey, Christian; Echterfeld, Julian; Reilender, Meikel; Gausemeier, Jürgen (Proceedings of the ISPIM connects)

Steigerung der Intelligenz mechatronischer Systeme - Gausemeier, Jürgen; Trächtler, Ansgar

Consumer Responses to Paid Search - Empirical Evidence from a Bricks-and-Mortar Retailer - Schlangenotto, Darius

Vorausschau und Technologieplanung - Gausemeier, Jürgen; Bauer, Wilhelm; Dumitrescu, Roman

Strategische kompetenzorientierte Ausrichtung der Wertschöpfungsstruktur aus Perspektive der Produktion - Altemeier, Björn; Gausemeier, Pia; Sickmann, Sebastian; Frank, Maximilian (Vorausschau und Technologieplanung, Symposium für Vorausschau und Technologieplanung, Band 385)
Die Umgestaltung einer Lagerproduktion zur kundenauftragsorientierten Produktion ist das definierte strategische Ziel des Produktionsbereichs Professional bei Miele & Cie. in Bielefeld. In Bielefeld werden Geräte der Spül- und Medizintechnik mit sehr hoher Wertschöpfungstiefe und in kleinen Stückzahlen produziert. Die Tendenz zur weiteren Verkleinerung der Los- und Auftragsgrößen ist jedoch steigend. Daher sind Produktivitätssteigerungen in diesem Umfeld nur durch eine kontinuierliche Reduzierung der Durchlaufzeit möglich. Dies bedingt eine Verbes-serung der Anlagen- und Personalflexibilität, der Stabilität der Teileversorgung und der Qualität der produzierten Bauteile und Endgeräte. Neben den hohen Qualitätsanforderungen an Miele Produkte führt im Bereich Professional zusätzlich das Medizinproduktegesetz zu einer hohen Komplexität der gefertigten Produkte. Deshalb kommt der Kompetenz der Mitarbeiter in der Produktion eine zentrale Rolle zu. Die Betrachtung des gesamten Wertstroms vom Lieferanten bis zum Kunden ist bei der strategischen kompetenzorientierten Ausrichtung der Wertschöpfungsstruktur unerlässlich. Deshalb wurde im ersten Schritt die Ist-Situation der Wertschöpfungsstruktur und der eingesetzten Technologien analysiert. Anschließend wurden die Technologien hinsichtlich ihrer strategischen Relevanz und der in der Professional Produktion vorhandenen Kompetenzen bewertet. Für hierdurch priorisierte Technologien wurden mögliche alternative Technologien ermittelt. Vor dem Hintergrund der Kompetenzplanung konnte letztlich entschieden werden, welche Technologien selbst eingesetzt und welche Produktionsschritte zu Lieferanten ausgelagert werden. Der Beitrag stellt sowohl die hierzu entwickelte Methode als auch die Ergebnisse aus der Validierung für die Ausrichtung der Professional Produktion in Bielefeld dar.

Digital B2B-Platforms and how to find the right one - Drewel, Marvin; Gausemeier, Jürgen (Proceedings of 13th European Conference on Innovation and Entrepreneurship)

Systematik zur zukunftsorientierten Konsolidierung variantenreicher Produktprogramme - Dülme, Christian

Systematik zur Positionierung in technologieinduzierten Wertschöpfungsnetzwerken - Kage, Martin

Applying Open Innovation in the Field of Aircraft MRO - Insights from the LOMIS Project - Pieper, Thorsten; Echterfeld, Julian; Koldewey, Christian (Book of Abstracts of the 16th International Open and User Innovation Conference, 6. - 8. Aug. 2018)

Planning of scalable Smart Services - Koldewey, Christian; Frank, Maximilian; Gausemeier, Jürgen (Proceedings of the 2018 ISPIM Innovation Conference)

Smart Services - Konzept einer neuen Marktleistung - Frank, Maximilian; Koldewey, Christian; Rabe, Martin; Dumitrescu, Roman; Gausemeier, Jürgen; Kühn, Arno (ZWF Zeitschrift für wirtschaftlichen Fabrikbetrieb 113(5))
Smart Services sind digitale Dienstleistungen, die aus den Daten einer Sachleistung Mehrwert generieren. Durch eine übersichtliche Abgrenzung der kursierenden Begrifflichkeiten tragen wir zum Verständnis dieser neuartigen Marktleistung bei. Wir zeigen eine Referenzarchitektur und postulieren vier Hauptherausforderungen: Konzipierung, Kompetenzen, Skalierung, strategische Planung.

Approach for a Pattern-Based Development of Frugal Innovations - Lehner, Anne-Christin; Koldewey, Christian; Gausemeier, Jürgen (Technology Innovation Management Review 8(4))

Innovationen im Zeitalter der Digitalisierung - Gausemeier, Jürgen; Dumitrescu, Roman (Industrie 4.0 Management 2.2018)

Zukunftsorientierte Leistungssteigerung von Unternehmen durch Industrie 4.0 - Pierenkemper, Christoph; Drewel, Marvin; Gausemeier, Jürgen (Tagungsband AALE 2018 - Das Forum für Fachleute der Automatisierungstechnik aus Hochschulen und Wirtschaft, 15. Konferenz für Angewandte Automatisierungstechnik in Lehre und Entwicklung (AALE))

Methodik zur Einführung innovativer Geschäftsmodelle in etablierten Unternehmen - Echterhoff, Benedikt

Strategische Planung - Gausemeier, Jürgen; Eckelt, Daniel; Dülme, Christian (Handbuch Gestaltung digitaler und vernetzter Arbeitswelten, Kapitel: Strategische Planung)

Spezifikationstechnik zur Beschreibung und Analyse von Wertschöpfungssystemen - Schneider, Marcel

Systematik zur geschäftsmodellorientierten Technologiefrühaufklärung - Placzek, Markus

Die Zukunft vorausdenken und gestalten - Siebe, Andreas; Backs, Sabrina; Echterhoff, Benedikt; Frank, Maximilian; Günther, Markus; Korsmeier, Kristin; Lüpke, Lars; Michl, Christian; Schmidt, Jens; Stummer, Christian (Intelligente Technische Systeme - Lösungen aus dem Spitzencluster it's OWL)

Einordnung der Beispiele der Industrie 4.0-Landkarte in die Anwendungsszenarien - Fay, Alexander; Gausemeier, Jürgen; ten Hompel, Michael

Leistungssteigerung durch Industrie 4.0 für kleine und mittlere Unternehmen - Knospe, Olaf; Drewel, Marvin; Mittag, Tobias; Pierenkemper, Christoph; Hobscheidt, Daniela (ZWF - Zeitschrift für Wirtschaftlichen Fabrikbetrieb 113 (1-2))

Peer Learning im Lehramtsstudium – Praxisbeispiel einer diversitysensiblen Lernbegleitung im Fach Hauswirtschaft - Hellweg, Joanna (Peer Learning an Hochschulen. Element einer diversitysensiblen, inklusiven Bildung)

Konsum, Ernährung und Gesundheit als zentrale Handlungsfelder für die alltägliche Lebensführung - Schlegel-Matthies, Kirsten (Haushalt in Bildung und Forschung (HiBiFo))
Der Artikel diskutiert zunächst Ziele, Aufgaben und Anforderungen an alltägliche Lebensführung und -gestaltung. Im Anschluss werden vor allem Wechselbeziehungen zwischen Entwicklungen und Strukturen in Wirtschaft, Gesellschaft und Politik einerseits und individueller Lebensführung andererseits betrachtet.

Das Lernzentrum Ernährung, Konsum, Gesundheit (LEKG) - Schlegel-Matthies, Kirsten; Hellweg, Joanna (Heterogenität als Chance. Bilanz und Perspektiven des Qualitätspakt Lehreprojekts an der Universität Paderborn)

„Keine Zeit!?“ – Über den Umgang mit einer kostbaren Ressource - Raacke, Georg (Alltägliche Lebensführung im Zusammenspiel von Individuum und Gesellschaft)
Zeit ist eine wichtige Ressource. Viele Menschen haben oft das Gefühl, die Zeit renne ihnen davon. Dabei ist Zeit auch immer eingebunden in gesellschaftliche Praxis. Während in der Vormoderne die Natur maßgeblich für die Bestimmung der Zeit war, brachte die Erfindung der Uhr ein völlig anderes Verständnis von Zeit und entsprechend von Zeithandeln. Zeit wurde nicht mehr als zyklisch verstanden, sondern als linearer Ablauf von Ereignissen. Heute gilt nicht mehr ausschließlich die Zeit der Uhr, Menschen sollen vielmehr flexibel ihre Zeit nutzen. Das hat nicht zuletzt eine unmittelbare Bedeutung für die alltägliche Lebensführung.

Polygene Formen der Adipositas und Störungs-übergreifende Analysen - Giuranna, J.; Antel, J.; Libuda, Lars; Reinehr, T.; Peters, T.; Hebebrand, J.; Hinney, A. (Adipositas - Ursachen, Folgeerkrankungen, Therapie)
Zusammenfassung Neben monogenen Formen und Hauptgen-Effekten sind für die genetische Prädisposition zur Adipositas polygene Mechanismen relevant. Meta-Analysen von genom-weiten Assoziationsstudien (GWAMA) haben mehr als 700 polygene Loci oder Polygene identifiziert, die genom-weit mit dem Body Mass index (BMI) assoziiert sind. Diese prädisponierenden Genvarianten (Allele) finden sich bei adipösen Probanden häufiger als bei normalgewichtigen oder schlanken Individuen. Mittels statistischer Analysen wurden diese Allele als Adipositas-Risikoallele klassifiziert. Jede einzelne polygene Variante leistet nur einen kleinen Beitrag zur Entwicklung einer Adipositas und erhöht das Gewicht pro Risikoallel nur um ca. hundert Gramm bis 1,5 Kilogramm. Der Erfolg der GWAMA hat in letzter Zeit Phänotyp übergreifende, sogenannte Cross- Disorder- und Cross-Phänotyp-Analysen, ermöglicht. Dabei können Risiko-Gene identifiziert werden, die mittels Analysen der einzelnen Erkrankungen / Phänotypen nicht entdeckt werden konnten. Funktionelle Studien (in vitro und in vivo) der GWAMA-abgeleiteten Polygene können zu einem besseren Verständnis der Mechanismen der Körpergewichtsregulation führen.

Trinken – was und wie viel? - Hilbig, A.; Libuda, Lars; Kalhoff, H. (Kinder- und Jugendmedizin)
Zusammenfassung Wasser ist für Menschen das wichtigste Nahrungsmittel. Die Verfügbarkeit von ausreichend Trinkwasser in hoher Qualität hat große Bedeutung und ist weltweit ein herausforderndes Entwicklungsziel. Wasser hat im Körper viele Funktionen, etwa als Baustoff, Reaktionsmedium und Reaktionspartner oder als wichtiges Transportmedium. Ein gut regulierter Wasserhaushalt ist Voraussetzung für normale Körperfunktionen und für langfristige Gesundheit. Eine Dehydratation kann zu Symptomen wie Schwäche, niedrigem Blutdruck und Hypotonie führen und die Bewusstseinslage beeinträchtigen. Ein vollständiger Wasserentzug ist schon nach Tagen tödlich. Aber auch eine leichte Dehydratation beeinträchtigt langfristig die körperliche und geistige Leistungsfähigkeit. Angaben zum täglichen Wasserbedarf stützen sich vornehmlich auf epidemiologisch ermittelte Zufuhrdaten, die für gesunde Kinder und Jugendliche adäquat sind. Im Durchschnitt sollten Schulkinder etwa einen Liter und Jugendliche etwa 1,5 Liter täglich trinken. Zuckergesüßte Getränke mit hoher Energiedichte könnten das Risiko für Übergewicht und Adipositas erhöhen. Ein gesunder Getränkeverzehr kann mit Maßnahmen zur Verhaltensund zur Verhältnisprävention gefördert werden.

Mandatory CSR reporting—literature review and future developments in Germany - Gulenko, Maryna (NachhaltigkeitsManagementForum | Sustainability Management Forum)

Failure behavior of short glass fiber reinforced polyamide under superimposed mechanical-enviromental fatigue - Brandler , Patrick R.

Analyse und Modellierung des Reckverfahrens von mono- und biaxial verstreckten Polypropylenfolien - Reinders , Frauke

Charakterisierung des Bruchverhaltens von Polypropylen-Celluloseregeneratfaser-Verbunden - Zarges, Jan-Christoph

Inverse thermische Spritzgießwerkzeugauslegung auf Basis des lokalen Kühlbedarfs - Nikoleizig , Philipp Alexander

Effects of breastfeeding on health outcomes in childhood: beyond dose-response relations - Buyken, Anette; Karaolis-Danckert, Nadina; Günther, Anke; Kersting, Mathilde (The American Journal of Clinical Nutrition)

Habitual Flavonoid Intake from Fruit and Vegetables during Adolescence and Serum Lipid Levels in Early Adulthood: A Prospective Analysis - Penczynski, Katharina; Remer, Thomas; Herder, Christian; Kalhoff, Hermann; Rienks, Johanna; Markgraf, Daniel; Roden, Michael; Buyken, Anette (Nutrients)

In adolescence a higher ‘eveningness in energy intake’ is associated with higher total daily energy intake - Diederichs, Tanja; Perrar, Ines; Roßbach, Sarah; Alexy, Ute; Buyken, Anette (Appetite)

Positive Effects of Practical Nutrition Lessons in a Primary SchoolSetting with a High Proportion of Migrant School Children - Weber, Katharina S.; Eitner, Jessica; Dauben, Laura; Spörkel, Olaf; Strassburger, Klaus; Sommer, Jörn; Kaiser, Barbara; Buyken, Anette; Kronsbein, Peter; Müssig, Karsten (Experimental and Clinical Endocrinology & Diabetes)
Abstract Background Children with migration background are at increased risk for overweight, partly due to less favorable dietary habits compared to their German counterparts. We examined the effects of practical nutrition lessons among children with a high proportion of migration background in a primary school setting. Methods Ten 3rd and 4th grade classes (n=166 children, 73% with migration background) received the intervention and nine school classes (n=139 children, 76% with migration background) served as control. Before, shortly after (only among the intervention group) and three months after the three-day practical nutrition lessons, the nutrition-related skills, behavior, attitudes, and knowledge of the children were assessed using a questionnaire. Changes between baseline and 1st follow-up among children of the intervention group were calculated using linear mixed models. Differences between the two groups for changes between baseline and 2nd follow-up were tested using linear regression analyses. Models were adjusted for potential confounders. Results Shortly after the practical nutrition lessons, the children of the intervention group had improved their knowledge (β=1.7; 95% CI: 1.0; 2.4, P<0.001) and skills (β=1.8; 95% CI: 1.4; 2.2, P<0.001). These changes were sustainable and larger in the intervention compared to the control group (knowledge: β=1.6; 95% CI: 0.7; 2.5, P<0.001; skills: β=1.3; 95% CI: 0.7; 1.9, P<0.001). Changes in nutrition-related behavior and attitudes did not differ between the groups. Conclusions Providing practical nutrition lessons in a primary school setting with a high proportion of children with immigrational background improved the children’s nutrition-related knowledge and skills.

Time and age trends in morning and evening protein intakes of German children and adolescents - Roßbach, Sarah; Diederichs, Tanja; Herder, Christian; Buyken, Anette; Alexy, Ute (Journal of Nutritional Science)
Abstract The present study describes time and age trends in morning and evening protein intakes and sources among German children and adolescents from 1985 to 2014. A total of 9757 three-day weighed dietary records of 1246 3- to 18-year-old participants of the Dortmund Nutritional and Anthropometric Longitudinally Designed (DONALD) study were analysed using polynomial mixed-effects regression models. Morning protein intake increased over the study period by approximately 1 % of morning energy intake (linear trend P < 0·0001), with the youngest and the oldest children having the highest protein intake (linear, quadratic trend P < 0·0001). Evening protein intake increased over time by approximately 2 % of evening energy intake in girls (linear trend P < 0·0001) and 1 % of evening energy intake in boys (quadratic trend P = 0·0313), with decreasing intake with age (girls: linear trend P < 0·0001; boys: linear trend P = 0·0963). Time trends were largely due to increases in protein from ‘starchy foods’. In conclusion, morning and evening protein intakes increased modestly between 1985 and 2014; these increases were, however, not accompanied by increases in traditional protein sources (i.e. meat or dairy products).

Schule und Bildungsadministration im Dialog – Eine qualitative Untersuchung über die Kooperation zwischen der schulischen Praxis und der Qualitäts- und Unterstützungsagentur NRW - Drossel, Kerstin (Does ‚What works‘ work? – Bildungsforschung, Bildungsadministration und Bildungspolitik im Dialog)

Die Relevanz schulischer IT-Ausstattungskonzepte für die Implementierung neuer Technologien in Schulen - Eickelmann, Birgit; Drossel, Kerstin; Gerick, Julia (Medien und Erziehung)

Determinanten der unterrichtlichen Computernutzungshäufigkeit und der medienbezogenen Kooperation. Eine Analyse auf Grundlage des Länderindikators 'Schule digital' - Drossel, Kerstin; Eickelmann, Birgit; Lorenz, Ramona (Unterrichtswissenschaft)

Eine geschlechtsspezifische Analyse zum schulischen Erwerb computerbezogener Kompetenzen in Tablet-Klassen am Gymnasium - Massek, Corinna; Drossel, Kerstin; Eickelmann, Birgit (MedienImpulse)
Aufgrund gesellschaftlicher Veränderungen und der steigenden Relevanz eines kompetenten, selbstbestimmten und reflektierten Umgangs mit digitalen Medien, ergeben sich auch für Schulen neue Herausforderungen, den Erwerb entsprechender Kompetenzen zu unterstützen. Studien deuten bzgl. des Kompetenzerwerbs auf Disparitäten zwischen Mädchen und Jungen hin – Mädchen schneiden in computer- und informationsbezogenen Kompetenzen besser ab und geben zu höheren Anteilen an, diese Kompetenzen schulisch erworben zu haben. Hinsichtlich der Vermittlung dieser Kompetenzen deuten aktuelle Entwicklungen darauf hin, dass Schulen vermehrt auf 1:1-Ausstattung mit digitalen Medien setzen, da vor allem schülereigenen mobilen Endgeräten vielseitige Potenziale zugeschrieben werden. Der Beitrag fokussiert daher auf Grundlage eines Tablets-Projekts die Frage, ob die Einführung schülereigener Tablets den schulischen Kompetenzerwerb für Mädchen und Jungen tatsächlich unterstützt. Im Ergebnis zeigt sich, dass die Einführung von Tablets nicht automatisch dazu führt, dass Mädchen und Jungen gleichermaßen einen schulischen Kompetenzerwerb wahrnehmen.

Digitale Medien in TIMSS 2015 und IGLU 2016. Ergebnisse zur Nutzung und zum Stellenwert von Lehrerfortbildungen für Grundschulen in Deutschland im internationalen Vergleich - Eickelmann, Birgit; Drossel, Kerstin (SchulVerwaltung NRW)

Die Rolle der Lehrerprofessionalisierung für die Implementierung neuer Technologien in den Unterricht – Eine Latent-Class-Analyse zur Identifikation von Lehrertypen - Drossel, Kerstin; Eickelmann, Birgit (MedienPädagogik: Zeitschrift für Theorie und Praxis der Medienbildung)
Mangelnde medienpädagogische Kompetenzen stellen für Lehrpersonen einen Hemmfaktor dar, digitale Medien in unterrichtliche Lehr-Lernprozesse zu integrieren. Fortbildungen sowie Lehrerkooperationen bieten in diesem Kontext Ansatzpunkte für Lehrerprofessionalisierungsmassnahmen (Drossel et al. 2016; Herzig 2007; Weiß und Bader 2010). Im internationalen Vergleich zeigt sich jedoch, dass Lehrpersonen in Deutschland selten an Professionalisierungsmassnahmen teilnehmen (Gerick et al. 2014).
Bisherige Befunde berücksichtigen allerdings nicht, dass das medienpädagogische Professionalisierungsverhalten stark variiert (Lorenz et al. 2016), was sich vermutlich in unterschiedlicher Weise auf die unterrichtliche Nutzung digitaler Medien auswirkt. Dieses Forschungsanliegen greift dieser Beitrag auf Grundlage von Sekundäranalysen der Lehrerdaten (N=1.377) der IEA-Studie ICILS 2013 (Bos, Eickelmann et al. 2014) auf und untersucht entlang des theoretischen Rahmenmodells der Studie, ob sich in Deutschland hinsichtlich der Professionalisierung Lehrertypen identifizieren lassen und welcher Zusammenhang zur unterrichtlichen Nutzung digitaler Medien sowie zu weiteren Prädiktoren der Mediennutzung besteht.
Anhand einer Latent Class Analyse können zwei Gruppen identifiziert werden: die zurückhaltenden (85%) sowie die engagierten Professionalisierer (15%). Die Professionalisierung beider Gruppen erfolgt eher im internen Bereich, wobei sie bei den engagierten Professionalisierern höher ausfällt. Engagierte Professionalisierer nutzen zudem häufiger digitale Medien im Unterricht, schätzen ihre computerbezogenen Fähigkeiten höher ein und geben in einem höheren Masse an, die computerbezogenen Kompetenzen der Schülerschaft zu fördern.

Distributed Algorithms for Overlay Networks and Programmable Matter - Gmyr, Robert

Self-Stabilizing Supervised Publish-Subscribe Systems - Feldmann, Michael; Kolb, Christina; Scheideler, Christian; Strothmann, Thim Frederik (Proceedings of the 32nd IEEE International Parallel & Distributed Processing Symposium (IPDPS))
In this paper we present two major results: First, we introduce the first self-stabilizing version of a supervised overlay network (as introduced in~\cite{DBLP:conf/ispan/KothapalliS05}) by presenting a self-stabilizing supervised skip ring. Secondly, we show how to use the self-stabilizing supervised skip ring to construct an efficient self-stabilizing publish-subscribe system. That is, in addition to stabilizing the overlay network, every subscriber of a topic will eventually know all of the publications that have been issued so far for that topic. The communication work needed to processes a subscribe or unsubscribe operation is just a constant in a legitimate state, and the communication work of checking whether the system is still in a legitimate state is just a constant on expectation for the supervisor as well as any process in the system.
Keywords: Topological Self-stabilization; Supervised Overlay; Publish-Subscribe System

Skueue: A Scalable and Sequentially Consistent Distributed Queue - Feldmann, Michael; Scheideler, Christian; Setzer, Alexander (Proceedings of the 32nd IEEE International Parallel & Distributed Processing Symposium (IPDPS))
We propose a distributed protocol for a queue, called Skueue, which spreads its data fairly onto multiple processes, avoiding bottlenecks in high throughput scenarios. Skueuecan be used in highly dynamic environments, through the addition of join and leave requests to the standard queue operations enqueue and dequeue. Furthermore Skueue satisfies sequential consistency in the asynchronous message passing model. Scalability is achieved by aggregating multiple requests to a batch, which can then be processed in a distributed fashion without hurting the queue semantics. Operations in Skueue need a logarithmic number of rounds w.h.p. until they are processed, even under a high rate of incoming requests.

Making the Case for Proof-carrying Approximate Circuits - Witschen, Linus Matthias; Wiersema, Tobias; Platzner, Marco (4th Workshop On Approximate Computing (WAPCO 2018))

Tomography and Purification of the Temporal-Mode Structure of Quantum Light - Ansari, Vahid; Donohue, John M.; Allgaier, Markus; Sansoni, Linda; Brecht, Benjamin; Roslund, Jonathan; Treps, Nicolas; Harder, Georg; Silberhorn, Christine (Physical Review Letters)

Tailoring nonlinear processes for quantum optics with pulsed temporal-mode encodings - Ansari, Vahid; Donohue, John M.; Brecht, Benjamin; Silberhorn, Christine (Optica)

Ensembles of Evolved Nested Dichotomies for Classification - Wever, Marcel Dominik; Mohr, Felix; Hüllermeier, Eyke (Proceedings of the Genetic and Evolutionary Computation Conference, GECCO 2018, Kyoto, Japan, July 15-19, 2018)
In multinomial classification, reduction techniques are commonly used to decompose the original learning problem into several simpler problems. For example, by recursively bisecting the original set of classes, so-called nested dichotomies define a set of binary classification problems that are organized in the structure of a binary tree. In contrast to the existing one-shot heuristics for constructing nested dichotomies and motivated by recent work on algorithm configuration, we propose a genetic algorithm for optimizing the structure of such dichotomies. A key component of this approach is the proposed genetic representation that facilitates the application of standard genetic operators, while still supporting the exchange of partial solutions under recombination. We evaluate the approach in an extensive experimental study, showing that it yields classifiers with superior generalization performance.
Keywords: Classification; Hierarchical Decomposition; Indirect Encoding

If You Ask Nicely: A Digital Assistant Rebuking Impolite Voice Commands - Bonfert, Michael; Spliethöver, Maximilian; Arzaroli, Roman; Lange, Marvin; Hanci, Martin; Porzel, Robert (Proceedings of the 20th ACM International Conference on Multimodal Interaction)

Influence of sp3/sp2-carbon ratio of vertically standing carbon nanostructures produced by pulsed laser-treatment on PAN-based carbon fibers - Engelkemeier, Katja; Hoyer, Kay-Peter; Schaper, Mirko (Materials Letters)

Top-down design of tailored fiber-metal laminates - Camberg, Alan A.; Engelkemeier, Katja; Dietrich, Jan; Heggemann, Thomas (Lightweight Design worldwide)

Anodizing of electrolytically galvanized steel surfaces for improved interface properties in fiber metal laminates - Engelkemeier, Katja; Mücke, Christian; Hoyer, Kay Peter; Schaper, Mirko (Advanced Composites and Hybrid Materials)

Einsatz von Spielmechaniken und Bots zur Moderation von Kreativitätsprozessen in Unternehmen - Mirbabaie, Milad; Stieglitz, Stefan; Priesmeyer, Jessica; Kindel, Marius (HMD Praxis der Wirtschaftsinformatik)

Social Media Analytics - Challenges in Topic Discovery, Data Collection, and Data Preparation - Stieglitz, S.; Mirbabaie, Milad; Ross, B.; Neuberger, C. (International Journal of Information Management)

Going Back in Time to Predict the Future - The Complex Role of the Data Collection Period in Social Media Analytics - Stieglitz, S.; Meske, C.; Ross, B.; Mirbabaie, Milad (Information Systems Frontiers)

Understanding Sense-Making on Social Media during Crises: Categorization of Sense-Making Barriers and Strategies - Stieglitz, S.; Mirbabaie, Milad; Fromm, J. (International Journal of Information Systems for Crisis Response and Management)

Interaction and Influence on Twitter: Comparing the discourse relationships between user types on five topics - Kapidzic, Sanja; Neuberger, Christoph; Stieglitz, Stefan; Mirbabaie, Milad (Digital Journalism)

Social Positions and Collective Sense-making in Crisis Communication - Stieglitz, S.; Mirbabaie, Milad; Milde, M. (International Journal of Human-Computer Interaction)

Information Diffusion between Twitter and Online Media - Jung, A.-K.; Mirbabaie, Milad; Ross, B.; Stieglitz, S.; Neuberger, C.; Kapidzic, S. (Proceedings of the 39th International Conference on Information Systems)

The Potential of Social Media Analytics for Improving Social Media Communication of Emergency Agencies - Mirbabaie, Milad; Fromm, J.; Löppenberg, S.; Meinig, S.; Reuße, M. (Proceedings of the 29th Australasian Conference on Information Systems)

Sense-Giving Strategies of Media Organisations in Social Media Disaster Communication: Findings from Hurricane Harvey - Marx, J.; Mirbabaie, Milad; Ehnis, C. (Proceedings of the 29th Australasian Conference on Information Systems)

You are now an Influencer! Measuring CEO Reputation in Social Media - Marx, J.; Mirbabaie, Milad; Stieglitz, S. (Proceedings of the 29th Australasian Conference on Information Systems)

Threat or Opportunity? - Examining Social Bots in Social Media Crisis Communication - Brachten, F.; Mirbabaie, Milad; Stieglitz, S.; Berger, O.; Bludau, S.; Schrickel, K. (Proceedings of the 29th Australasian Conference on Information Systems)

The Adoption of Social Media Analytics for Crisis Management – Challenges and Opportunities - Stieglitz, S.; Mirbabaie, Milad; Fromm, J.; Melzer, S. (Proceedings of the Twenty-Sixth European Conference on Information Systems)

"Is it really fake? – Towards an Understanding of Fake News in Social Media Communication" - Meinert, J.; Mirbabaie, Milad; Dungs, S.; Aker, A. (20th International Conference on Human-Computer Interaction, Social Computing and Social Media)

The Quality of Tweets and the Adoption of Journalistic Norms - Kapidzic, Sanja; Neuberger, Christoph; Stieglitz, Stefan; Mirbabaie, Milad (Trust in Media and Journalism: Empirical perspectives on ethics, norms, impacts and populism in Europe)

Exploring Sense-making Activities in Crisis Situations - Mirbabaie, Milad; Youn, S. (Proceedings of the 10th Multikonferenz Wirtschaftsinformatik)

Integration von Social-Media-Daten in analytische CRM-Systeme - Mirbabaie, Milad; Potthoff, T.; Lange, C.; Stieglitz, S. (Proceedings of the 10th Multikonferenz Wirtschaftsinformatik)

Crisis Communication on Twitter during a Global Crisis of Volkswagen – The Case of “Dieselgate” - Stieglitz, S.; Mirbabaie, Milad; Potthoff, T. (Proceedings of the 51st Hawaii International Conference on System Sciences)

Koopman Operator-Based Finite-Control-Set Model Predictive Control for Electrical Drives - Hanke, Sören; Peitz, Sebastian; Wallscheid, Oliver; Klus, Stefan; Böcker, Joachim; Dellnitz, Michael (arXiv:1804.00854)
Predictive control of power electronic systems always requires a suitable model of the plant. Using typical physics-based white box models, a trade-off between model complexity (i.e. accuracy) and computational burden has to be made. This is a challenging task with a lot of constraints, since the model order is directly linked to the number of system states. Even though white-box models show suitable performance in most cases, parasitic real-world effects often cannot be modeled satisfactorily with an expedient computational load. Hence, a Koopman operator-based model reduction technique is presented which directly links the control action to the system's outputs in a black-box fashion. The Koopman operator is a linear but infinite-dimensional operator describing the dynamics of observables of nonlinear autonomous dynamical systems which can be nicely applied to the switching principle of power electronic devices. Following this data-driven approach, the model order and the number of system states are decoupled which allows us to consider more complex systems. Extensive experimental tests with an automotive-type permanent magnet synchronous motor fed by an IGBT 2-level inverter prove the feasibility of the proposed modeling technique in a finite-set model predictive control application.

Unterstützung des Forschungsprozesses aus infrastruktureller Sicht - Brennecke, Andreas; Oevel, Gudrun; Strauch, Thomas (STUDIOLO. Kooperative Forschungsumgebungen in den eHumanities)

IoT-ASAP 2018: Message from the Chairs - Spalazzese, Romina; Platenius, Marie C.; Becker, Steffen; Engels, Gregor (2018 IEEE International Conference on Software Architecture Companion (ICSA-C))

Approach for a Pattern-Based Development of Frugal Innovations - Lehner, Anne-Christin; Koldewey, Christian; Gausemeier, Jürgen (Technology Innovation Management Review)

Smart Services – Konzept einer neuen Marktleistung - Frank, Maximillian; Koldewey, Christian; Rabe, Martin; Dumitrescu, Roman; Gausemeier, Jürgen; Kühn, Arno (ZWF Zeitschrift für wirtschaftlichen Fabrikbetrieb)

What are the Drivers of Tax Complexity for MNCs? Global Evidence - Hoppe, Thomas; Sturm, Susann; Sureth-Sloane, Caren (Intertax)

Bridging - Fremdsprache und Fachwissenschaft. Digital Learning Map - Mindt, Ilka

Metasurface holography: from fundamentals to applications - Huang, Lingling; Zhang, Shuang; Zentgraf, Thomas (Nanophotonics)

Removing Undesirable Flows by Edge Deletion - Polevoy, Gleb; Trajanovski, Stojan; Grosso, Paola; de Laat, Cees (Combinatorial Optimization and Applications)
Consider mitigating the effects of denial of service or of malicious traffic in networks by deleting edges. Edge deletion reduces the DoS or the number of the malicious flows, but it also inadvertently removes some of the desired flows. To model this important problem, we formulate two problems: (1) remove all the undesirable flows while minimizing the damage to the desirable ones and (2) balance removing the undesirable flows and not removing too many of the desirable flows. We prove these problems are equivalent to important theoretical problems, thereby being important not only practically but also theoretically, and very hard to approximate in a general network. We employ reductions to nonetheless approximate the problem and also provide a greedy approximation. When the network is a tree, the problems are still MAX SNP-hard, but we provide a greedy-based 2l-approximation algorithm, where l is the longest desirable flow. We also provide an algorithm, approximating the first and the second problem within {\$}{\$}2 {\backslash}sqrt{\{} 2{\backslash}left| E {\backslash}right| {\}}{\$}{\$}and {\$}{\$}2 {\backslash}sqrt{\{}2 ({\backslash}left| E {\backslash}right| + {\backslash}left| {\backslash}text {\{}undesirable flows{\}} {\backslash}right| ){\}}{\$}{\$}, respectively, where E is the set of the edges of the network. We also provide a fixed-parameter tractable (FPT) algorithm. Finally, if the tree has a root such that every flow in the tree flows on the path from the root to a leaf, we solve the problem exactly using dynamic programming.
Keywords: flow; Red-Blue Set Cover; Positive-Negative Partial Set Cover; approximation; tree; MAX SNP-hard; root; leaf; dynamic programming; FPT

Measuring the efficiency of SDN mitigations against attacks on computer infrastructures - Koning, R.; de Graaff, B.; Polevoy, Gleb; Meijer, R.; de Laat, C.; Grosso, P. (Future Generation Computer Systems)
Software Defined Networks (SDN) and Network Function Virtualisation (NFV) provide the basis for autonomous response and mitigation against attacks on networked computer infrastructures. We propose a new framework that uses SDNs and NFV to achieve this goal: Secure Autonomous Response Network (SARNET). In a SARNET, an agent running a control loop constantly assesses the security state of the network by means of observables. The agent reacts to and resolves security problems, while learning from its previous decisions. Two main metrics govern the decision process in a SARNET: impact and efficiency; these metrics can be used to compare and evaluate countermeasures and are the building blocks for self-learning SARNETs that exhibit autonomous response. In this paper we present the software implementation of the SARNET framework, evaluate it in a real-life network and discuss the tradeoffs between parameters used by the SARNET agent and the efficiency of its actions.
Keywords: Software defined networks; Network function virtualization; Cyber attacks; Cyber security; Defense efficiency; Overlay networks

"Digital Humanitites: The Role of the Digital in English Philology". Sprachwissenschaftliche Sektion beim Anglistentag 2017 in Regensburg - Mindt, Ilka; Bartsch, Sabine (Anglistentag 2017 Regensburg. Proceedings)

Automated Multi-Label Classification based on ML-Plan - Wever, Marcel Dominik; Mohr, Felix; Hüllermeier, Eyke

Automated machine learning service composition - Mohr, Felix; Wever, Marcel Dominik; Hüllermeier, Eyke

BWL greift gesellschaftlichen Wandel auf - Wolff, Birgitta; Sureth-Sloane, Caren; Weissenberger, Barbara (Frankfurter Allgemeine Zeitung)

Englischer Sprachwandel im Zeitalter von Digitalisierung und Innovation - Mindt, Ilka (Paderborner Unireden 148)

Digital Humanities: The Role of the Digital in English Philology - Bartsch, Sabine; Mindt, Ilka (Anglistentag 2017 Regensburg. Proceedings)

Additive Manufacturing of Porous Structures for Unmanned Aerial Vehicles Applications - Klippstein, Sven Helge; Hassanin, Hany; Diaz De Cerio Sanchez, Alejandro; Zweiri, Yahya; Seneviratne, Lakmal (Advanced Engineering Materials)

Futurelab Medienpädagogik. Qualitätsentwicklung. Professionalisierung

Erkundungen in die Kunstgeschichte, Kirchenbau, Städtebau, Utopie, Sammelband von bislang meist unpublizierten Aufsätzen - Seng, Eva- Maria

Kultur, Natur, Ökologie. Die Pfahlbauten als Ausgangspunkt einer integralen Sicht auf Weltkulturerbestätten - Seng, Eva- Maria (Prähistorische Pfahlbauten im Alpenraum. Erschließung und Vermittlung des Welterbes)

以德国博物馆为例谈博物馆及其展览【德】伊娃- 玛利亚·森钟子溦 翻译 (Exhibitions in the Museum) - Seng, Eva- Maria (Tsinghua Art Museum TAM)

Kinder partizipativ in Forschung einbeziehen – ein kinderrechtsbasiertes Stufenmodell - Büker, Petra; Hüpping, Birgit; Mayne, Fiona; Howitt, Christine (Diskurs Kindheits- und Jugendforschung / Discourse. Journal of Childhood and Adolescence Research)

Literaturwissenschaft - Eke, Norbert Otto; Allkemper, Alo

Poster: CrossEcore: An Extendible Framework to Use Ecore and OCL across Platforms - Schwichtenberg, Simon; Jovanovikj, Ivan; Gerth, Christian; Engels, Gregor (Proceedings of the 40th International Conference on Software Engineering, ICSE 2018 - Companion Volume)
Today, model-driven approaches are a cornerstone in modern software development. The Eclipse Modeling Framework (EMF) is highly adopted in practice and generates Java code from platform-independent models with embedded Object Constraint Language (OCL) expressions. However, applications that target multiple platforms like Android, iOS, Windows, web browsers usually need to be implemented in different programming languages. Feature-complete Ecore and OCL runtime APIs are not available for all these platforms, such that their functionality has to be re-implemented. In this paper, we present CrossEcore: A multi-platform enabled modeling framework that generates C#, Swift, TypeScript, and JavaScript code from Ecore models with embedded OCL. An OCL compiler translates OCL expressions into expressions of the target language. The Ecore and OCL API can be consistently used across platforms, which facilitates application portability. CrossEcore is also extendible and can be easily adopted for new programming languages.

„Travelling memories“? Interkulturelle Akzentsetzungen in deutsch-jüdischer Literatur der zweiten Generation - Eke, Norbert Otto (Der Neue Weltengarten. Jahrbuch für Literatur und Interkulturalität 2017/2018)

Weltuntergänge. Heiner Müllers und Lothar Trolles (Welt-)Kriegsszenarien - Eke, Norbert Otto (Kriegstheater. Darstellungen von Krieg, Kampf und Schlacht in Drama und Theater seit der Antike)